Stratified Preoperative A1c is not Significantly Associated With Clavien-Dindo Major Complications Following Bariatric Surgery in the MBSAQIP Database. Issue 11 (November 2022) - Pina, Luis; Dove, James; Wood, G. Craig; Parker, David M.; Still, Christopher; Petrick, Anthony; Daouadi, Mustapha
Background: Type 2 Diabetes Mellitus (T2DM) is highly prevalent comorbidity in patients with morbid obesity. It is still unclear whether a cutoff value of preoperative A1c represents an increased risk for major postoperative complications following Roux-en-Y Gastric Bypass (RYGB) and Sleeve Gastrectomy (SG). Methods: Retrospective MBSAQIP Participant Use File cohort for both years 2017 and 2018 were analyzed to evaluate the relationship between HbA1c in patients with morbid obesity and T2DM undergoing bariatric surgery, and the 30 days postoperative major complications by Clavien-Dindo classification (III/IV). We used an HbA1c cutoff of <7, > =7, and stratified by 1% increment for a total of 11 groups. We used univariate and multivariate logistic regression to analyze the outcome of the complications. Predicted probabilities were calculated for major complications. All statistical tests were two-sided with a P -value of less than .05 considered as a cut-off for statistical significance. Results: Of 42, 181 patients that met inclusion criteria, there were 20, 955 identified with HbA1c <7%, and 21, 226 patients with HbA1c >7%. Utilizing HbA1c <7% as a cutoff, we found no consistent statistical significance in the major postoperative complication in patients with HbA1c >7%, and when stratified with 1% increment between groups. We also found no significance between groups with risk adjustment. Conclusions: Extensive analysis of the large MBSAQIP cohort didn't result in a clinically significant association between stratified HbA1c and 30-day Clavien-Dindo major complications (III/IV) following Roux-en-Y Gastric Bypass (RYGB) and (SG).